Facile preparation of robust and multipurpose microelectrodes based on injected epoxy resin. (1st January 2023) - Zhao, Ziwen; Martino, Nazario; Tagliabue, Luca; Minguzzi, Alessandro; Vertova, Alberto
Abstract: Conventional microdisk electrodes for scanning electrochemical microscopy -SECM- and for related techniques are mostly based on a metallic micro-wire insulated in a glass capillary. At one end, a section of the microwire is exposed, while the other end is used for the electric contact with the potentiostat/galvanostat. The preparation of these devices is time consuming and the resulting systems are fragile and thus not fully suitable for educational purposes. Commercial microelectrodes (SECM tips in particular) are expensive. In this work we introduce a method for rapidly preparing robust microdisk electrodes, based on insulation by epoxy resin (but easily adaptable to other polymers), that doesn't simply represent a technological advance in the field, but introduces a new technological platform, given the flexibility of the method.